2016
DOI: 10.1038/ijir.2016.5
|View full text |Cite
|
Sign up to set email alerts
|

Sexual quality of life is impaired in patients with chronic hepatitis C

Abstract: Chronic hepatitis C (CHC) patients often have altered quality of life. Few data are available about sexual impairment (SI) in CHC. From 2011 to 2013, we included consecutive CHC outpatients. Exclusion criteria were: antiviral therapy, co-infection, age <18 or >75, transplantation, alcohol consumption, Eastern Cooperative Oncology Group >1. Non-CHC subjects were healthy blood donors. Sexual questionnaires for men and women were adapted from the International Index of Erectile Function and Female Sexual Function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 15 publications
2
11
0
Order By: Relevance
“…[14][15][16]26 In chronic hepatitis, the prevalence ranged between 9% and 78% 15,26 with most studies reporting prevalence rates around 40%-50%. 16,17,[43][44][45] Hence, it seems that once cirrhosis develops, the prevalence of ED is high irrespective of aetiology and this is also confirmed by our data. To our best knowledge, only 2 studies investigated ED in non-alcoholic fatty liver disease and found a prevalence of 45% 46 and 67.5% 47 respectively.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…[14][15][16]26 In chronic hepatitis, the prevalence ranged between 9% and 78% 15,26 with most studies reporting prevalence rates around 40%-50%. 16,17,[43][44][45] Hence, it seems that once cirrhosis develops, the prevalence of ED is high irrespective of aetiology and this is also confirmed by our data. To our best knowledge, only 2 studies investigated ED in non-alcoholic fatty liver disease and found a prevalence of 45% 46 and 67.5% 47 respectively.…”
Section: Discussionsupporting
confidence: 89%
“…The prevalence of ED in alcoholic cirrhosis is described with 50%‐70% and with 40%‐92% in viral cirrhosis . In chronic hepatitis, the prevalence ranged between 9% and 78% with most studies reporting prevalence rates around 40%‐50% . Hence, it seems that once cirrhosis develops, the prevalence of ED is high irrespective of aetiology and this is also confirmed by our data.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…There is a large body of literature suggesting that those living with hepatitis C have a lower quality of life than the general population . Reduced health‐related, general and sexual quality of life have all been reported among people living with hepatitis C (measured by the Sickness Impact Profile, World Health Organization Quality of Life Assessment Brief scale, adaptations of the International Index of Erectile Function and Female Sexual Function Index respectively). Other metrics have also been used to highlight the impact of hepatitis C on patient‐report outcomes.…”
Section: Measuring the Personal Burden Of Hepatitis Cmentioning
confidence: 99%
“…On the contrary, there is a lack of qualitative researches on reporting sexual health of males and females with chronic diseases that consider their subjective experiences (17). Because a few studies exist on marital problems in patients with chronic hepatitis C (18)(19)(20), knowledge on marital problems of HBV carriers is limited. As hepatitis B infection is a confidential and unparalleled experience, to have a detailed understanding of the patients' marital challenges, which are the most confidential secrets of private life, using a qualitative approach will be helpful.…”
Section: Introductionmentioning
confidence: 99%